Analisis Hukum Ekonomi Syariah Terhadap Gadai dengan Jaminan Sepeda Motor yang Belum Lunas - Tamrin, Ali; Moch Uzeir Mustaqfirin; Fitrotul Wafiyah (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2024)
This study aims to determine how the practice of pawning with the collateral of motorised vehicles whose status has not been paid off, is there a default at the time of the pawn practice and how is the analysis of the perspective of sharia economic law? This is interesting to study because this kind of pawn practice is often carried out in the environment around us, while the permissibility and halalness are not yet clear, the researcher took the place and object of research at UD Rejeki Barokah in Kencong Village, East Kencong Hamlet, Kepung District, because the place received a pawn of motorised vehicles where the status of the vehicle has not been paid off. This type of research is case study research using a qualitative descriptive approach. With data collection using triangulation techniques, namely observation, interviews and documentation. The results of this study are the practices carried out, namely the initial stage of rahin must meet the requirements of UD Rejeki Barokah first, the second stage is checking the collateral starting from securities to the vehicle receipt number, the third stage is the process for disbursing loans to be given by murtahin, besides that there is a pawn guarantee that is pawned again by the murtahin if the pawned person is still unable to pay it. If there is a default, there is an additional time despensation given by the murtahin with the condition that he must pay compensation for the time he has missed and if the rahin cannot replace the loan by auctioning the vehicle to replace the loan money given, the practice is not in accordance with Islamic economic law. This is because a motorbike that is still on credit is a guarantee from a financial institution that provides a loan, so it cannot be pawned directly without approval from the financing party, besides that there are additional costs in redemption and collection of goods.